The research plan for 1973 and appraisal by the committee of sponsors - Corkindale, David; Kennedy, Sherril (Cranfield School of Management, 1973)
This report presents the Research plan for 1973 proposed to the committee of sponsors prior to its meeting in January 1973. The second part of the report summaries the discussions held during the sponsors' meeting. Theses discussions covered consideration of report numbers 1 and 2 as well as the research plan. The conclusion of the sponsors' meeting was that the research plan was fully endorsed and consderation was requested for the inclusion of one further topic.